2018
DOI: 10.3390/antibiotics7040096
|View full text |Cite
|
Sign up to set email alerts
|

First Description of Colistin and Tigecycline-Resistant Acinetobacter baumannii Producing KPC-3 Carbapenemase in Portugal

Abstract: Herein, we describe a case report of carbapenem-resistant Acinetobacter baumannii and Klebsiella pneumoniae isolates that were identified from the same patient at a Tertiary University Hospital Centre in Portugal. Antimicrobial susceptibility and the molecular characterization of resistance and virulence determinants were performed. PCR screening identified the presence of the resistance genes blaKPC-3, blaTEM-1 and blaSHV-1 in both isolates. The KPC-3 K. pneumoniae isolate belonged to the ST-14 high risk clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Liu et al 25 reported a plasmidial mcr- 1 gene in E. coli identified in raw meat, animals and humans conferring elevated MICs (8 µg/ml) to colistin. Plasmid-mediated resistance has epidemiological implications due to a facilitated way of spread, including K. pneumoniae, as seen previously with ESBL and KPC 26 .…”
Section: Discussionmentioning
confidence: 86%
“…Liu et al 25 reported a plasmidial mcr- 1 gene in E. coli identified in raw meat, animals and humans conferring elevated MICs (8 µg/ml) to colistin. Plasmid-mediated resistance has epidemiological implications due to a facilitated way of spread, including K. pneumoniae, as seen previously with ESBL and KPC 26 .…”
Section: Discussionmentioning
confidence: 86%
“…KPC-3 was detected in A. baumannii from an infected wound culture of a patient admitted to a university hospital in Portugal. The isolate accumulated carbapenem, tigecycline, and colistin resistance [60]. No other reports of KPC-producing A. baumannii exist in other countries.…”
Section: Acinetobactermentioning
confidence: 90%
“…This is a 10-kb Tn3-based transposon, delimited by two 39-bp imperfect inverted repeat sequences, that harbors, in addition to the KPC-2 gene, a transposase gene, a resolvase gene, and two novel insertion sequences known as ISKpn6 and ISKpn7 [56]. Besides Enterobacteriaceae, KPC has been described in P. aeruginosa from Brazil [57] and China [58], as well as in A. baumannii from Puerto Rico [59] and Portugal [60]. KPC-producing K. pneumoniae isolates may be deficient in OmpK35 and OmpK36, which are porins for carbapenem entry.…”
Section: Ambler Class a Carbapenemasesmentioning
confidence: 99%
“…In 2010, Robledo et al reported, for the first time, Ambler class A Klebsiella pneumoniae carbapenemase (KPC)-5 in MDR A. baumannii from Puerto Rico [137]. Additional reports described KPC-3 in A. baumannii a Portugese University hospital [138], and both KPC-2 and KPC-3 in isolates from Brazil [139]. In a recent meta-analysis about A. baumannii in burn injury patients, the prevalence of KPC was over 16% [140].…”
Section: Ambler Class a Enzymesmentioning
confidence: 99%